Statistical Study of Brucellosis in Dhi-Qar City - Malik, Sarah Saber; shahad, Rafal kadhim; Odeh, Dr. Diyaa Abed (Journal of Science in Medicine and Life, 2024)
The infectious illness known as brucellosis is brought on by the gram-negative Brucella bacteria. The present research aimed to: a) examine individuals afflicted with Malta fever over the period of 2018 to 2020, focusing on the illness's etiology, risk factors, modes of transmission, symptoms, diagnosis, prevention, and therapy. b) Research how age and gender affect the Brucellosis epidemic in Nasiriya City; c) Analyze the proportion of patients who recover and gather information on the incidence of morbidity and death. The Dhi Qar Health Department's Public Health Laboratory's Communicable Diseases Division is where the data were gathered. The results showed that there were 7, 43 cases in total between 2018 and 2020, and that age and gender had a discernible impact on the disease's morbidity rate in Nissiriya City. Furthermore, the findings showed that the mortality rate was not higher than 2%. concluded that public hygiene could manage the infection and it was not dangerous.